(untitled) (Marketing Journal, 2025)
Research into the economic potential of an enterprise is impossible without analyzing the use of production capacity. At the same time, the complexity of the analysis of production activities leads to the fact that researchers are limited only to the analy sis of economic and financial indicators. This article is devoted to improving the methodology for analyzing production potential based on studying the operation of the main equipment of an industrial enterprise. The article uses the operation of equipment at a carpet manufacturing plant as analysis materials.